â€œTHE INFLUENCE OF SERVICE MARKETING MIX ON SMARTFREN CUSTOMER LOYALTY (Study on Brawijaya University Student as the Smartfren Customers)â€ - Annisa, Dhiya Nur; Rahayu, Mintarti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The Purpose of this research is to examine the effect of Marketing Service Mix (7Ps) Product, Price, Place, Promotion, People, Process and Physical Evidence on Customer Loyalty at Brawijaya University as a Smartfren customer. In order to know the relationship that occur among the independent variable (Product, Price, Place, Promotion, People, Process and Physical Evidence) on customer loyalty the regression analysis, F test and T test were conducted. This research is exploratory research, in accordance with its purpose to explain the correlation and relation of some variables. Population and samples in this research is Brawijaya student as customers of PT Smartfren Telecom, Tbk.Â The sampling technique is purposive sampling and the research instruments were tested using the validity test, reliability test and classical assumption test. The hypothesis testing was using the F and T test to analyze the data to be used in multiple regression analysis. Multiple regressions showed that simultaneously, marketing service mix had significant effects to customer loyalty. While partially tested, the variable of marketing service mix had no significance effect on customer loyalty, only variable price, promotion and physical evidence has significance influence partially toward to customer loyalty in use mobile data product of PT. Smartfren Telecom, Tbk. Keywords: customer loyalty, marketing service mix (7Ps)